A Pediatric Case of Benign Episodic Unilateral Mydriasis with Clinical Characteristics Resembling Tadpole Pupil - Henneberg, Rebecca Lise Gammelgaard; Vandborg, Pernille Kure; Hansen, Jonas Kjeldbjerg (Journal of Pediatric Neurology, 2021)
Benign episodic unilateral mydriasis is an episodic disturbance with dilatation of the entire pupil, often lasting for hours. It occurs most frequently in women aged between 20 and 50 years and is closely associated with migraines. Only a few pediatric cases have been reported. The demographics of benign unilateral mydriasis correspond to another episodic disturbance of the pupil, the tadpole pupil. Also, the clinical similarities between the two conditions are numerous. However, tadpole pupil is an irregular distortion of the pupil lasting from seconds to minutes and occurring in clusters. We present a 16-year-old girl with benign unilateral mydriasis and migraine. Her episodes of mydriasis lasted from seconds to minutes, occurred in clusters, and were thus like episodes of tadpole pupil. Benign unilateral mydriasis presenting this way has not been reported previously. This observation links the phenotypes of benign unilateral mydriasis and tadpole pupil closer together. The given case provides new knowledge as it (i) expands the clinical spectrum of benign episodic unilateral mydriasis, (ii) links the phenotypes of benign unilateral mydriasis and tadpole pupil together, and (iii) in comparison with knowledge about autonomic failure in migraine patients may add to hypotheses on pathophysiology in both pupillary disorders.
Keywords: mydriasis; tadpole pupil; migraine; autonomic dysfunction; pediatric